2018
DOI: 10.1007/s00784-018-2604-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for tooth loss in community-dwelling Japanese aged 40 years and older: the Yamagata (Takahata) study

Abstract: Poor oral health habits and low educational status are the independent risk factors for having less than 20 teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 44 publications
4
21
0
Order By: Relevance
“…[17][18][19] A current smoking habit was significantly associated with having <20 teeth in 7,542 community-dwelling Japanese people aged 40 years and older (adjusted OR = 1.68, 95% CI = 1.41-1.99) in the Yamagata study. 6 Our results are consistent with those of the Yamagata study. Parity was significantly associated with the decreasing rate of current smoking in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[17][18][19] A current smoking habit was significantly associated with having <20 teeth in 7,542 community-dwelling Japanese people aged 40 years and older (adjusted OR = 1.68, 95% CI = 1.41-1.99) in the Yamagata study. 6 Our results are consistent with those of the Yamagata study. Parity was significantly associated with the decreasing rate of current smoking in our study.…”
Section: Discussionsupporting
confidence: 92%
“…29 However, no such association was found in the study of Ishikawa et al in Japan. 6 The third limitation is the validity of the self-reported number of teeth present. We previously confirmed the association between the actual and self-reported number of teeth present in a different study.…”
Section: Limitationsmentioning
confidence: 99%
“…For Uruguayan participants, Laguzzi et al [21] also reported that tooth loss was more common in people with a lower household income. Studies of Brazilians by Chalub et al [22] and of the middle-aged Japanese population by Ishikawa et al [23] and Ando et al [24] also reported that tooth loss was more common in people with lower education levels.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, most adults ≥30 years of age experience dental caries, and at least 40% of dentate adults aged ≥40 years have periodontal disease [17]. In addition, tooth loss increases starting at approximately 40 years of age [18]. Therefore, nurses should perform oral assessments and dental referrals for not only elderly inpatients but also younger generations to prevent dental diseases and tooth loss.…”
Section: Discussionmentioning
confidence: 99%